Comparison of the inter-item correlations of the Big Five Inventory-10 (BFI-10) between Western and non-Western contexts - Park, Joonha; Van den Broek, Karlijn; Bhullar, Navjot; Ogunbode, Charles A.; Schermer, Julie Aitken; Doran, Rouven; Ardi, Rahkman; Hanss, Daniel; Maran, Daniela Acquadro; Albzour, Mai; Aquino, Sibele D.; Ayanian, Arin H.; et al. (Personality and individual differences, 2022)
The Big Five Inventory-10 (BFI-10; Rammstedt & John, 2007) is one of many short versions of personality inventories that measure the Big Five trait dimensions. Short versions of scales often present methodological challenges as a trade-off for their convenience. Based on samples from 28 countries (N=10,560), the current study investigated inter-item correlations estimated using Omega coefficients within each of the five personality characteristics measured by the BFI-10. Results showed that inter-item correlations were significantly lower, in the sample data from non-Western countries compared with the Western countries, for three of the five personality traits, specifically Conscientiousness, Extraversion, and Emotional Stability. Our findings indicate that the psychometric challenges exist across different cultures and traits. We offer recommendations when using short-item scales such as BFI-10 in survey research.
Gesehen am 04.10.2021